Neurologic Complications of Patients With COVID-19 Requiring Extracorporeal Membrane Oxygenation: A Systematic Review and Meta-Analysis. (27th March 2023) - Li, Cathy Meng Fei; Densy Deng, Xiaoxiao; Ma, Yu Fei; Dawson, Emily; Li, Carol; Wang, Dong Yao; Huong, Lynn; Gofton, Teneille; Nagpal, Atul Dave; Slessarev, Marat
Abstract : OBJECTIVES: In COVID-19 patients requiring extracorporeal membrane oxygenation (ECMO), our primary objective was to determine the frequency of intracranial hemorrhage (ICH). Secondary objectives were to estimate the frequency of ischemic stroke, to explore association between higher anticoagulation targets and ICH, and to estimate the association between neurologic complications and in-hospital mortality. DATA SOURCES: We searched MEDLINE, Embase, PsycINFO, Cochrane, and MedRxiv databases from inception to March 15, 2022. STUDY SELECTION: We identified studies that described acute neurological complications in adult patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection requiring ECMO. DATA EXTRACTION: Two authors independently performed study selection and data extraction. Studies with 95% or more of its patients on venovenous or venoarterial ECMO were pooled for meta-analysis, which was calculated using a random-effects model. DATA SYNTHESIS: Fifty-four studies ( n = 3, 347) were included in the systematic review. Venovenous ECMO was used in 97% of patients. Meta-analysis of ICH and ischemic stroke on venovenous ECMO included 18 and 11 studies, respectively. The frequency of ICH was 11% (95% CI, 8–15%), with intraparenchymal hemorrhage being the most common subtype (73%), while the frequency of ischemic strokes was 2% (95% CI, 1–3%). Higher anticoagulation targets were not associated with increased frequency of ICH ( p = 0.06). In-hospital mortality was 37% (95% CI, 34–40%) and neurologic causes ranked as the third most common cause of death. The risk ratio of mortality in COVID-19 patients with neurologic complications on venovenous ECMO compared with patients without neurologic complications was 2.24 (95% CI, 1.46–3.46). There were insufficient studies for meta-analysis of COVID-19 patients on venoarterial ECMO. CONCLUSIONS: COVID-19 patients requiring venovenous ECMO have a high frequency of ICH, and the development of neurologic complications more than doubled the risk of death. Healthcare providers should be aware of these increased risks and maintain a high index of suspicion for ICH.